2012
DOI: 10.1007/s12020-012-9744-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose control in diabetes: the impact of racial differences on monitoring and outcomes

Abstract: Purpose Type 2 diabetes is the seventh leading cause of death in the US and is projected to increase in prevalence globally. Minorities are disproportionately affected by diabetes and data suggest that clinical outcomes consistently fall below American Diabetes Association recommendations. The purpose of this systematic review was to examine ethnic differences in self-monitoring and outcomes in adults with type 2 diabetes. Methods Medline was searched for articles published between January 1990 through Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 25 publications
0
72
1
1
Order By: Relevance
“…(10) Despite varying research designs, sample sizes, source data, and study limitations, members within minority populations (African Americans, Hispanic, and Asian Americans) were found to have significantly higher HbA1c levels compared to non-Hispanic Whites. (10) Additionally, regardless of the study population and the measured outcome (i.e., HbA1c threshold of <7% vs. <9%), differences in glycemic control by race and ethnicity were observed, and these differences were clinically significant indicated by a difference in HbA1c by a minimum of 0.5 between groups. (10) Finally, a persistent racial gap in glycemic control between African Americans and non-Hispanic Whites was continually observed in the populations assessed during the systematic review.…”
Section: Racial Differences In Diabetes Outcomesmentioning
confidence: 99%
“…(10) Despite varying research designs, sample sizes, source data, and study limitations, members within minority populations (African Americans, Hispanic, and Asian Americans) were found to have significantly higher HbA1c levels compared to non-Hispanic Whites. (10) Additionally, regardless of the study population and the measured outcome (i.e., HbA1c threshold of <7% vs. <9%), differences in glycemic control by race and ethnicity were observed, and these differences were clinically significant indicated by a difference in HbA1c by a minimum of 0.5 between groups. (10) Finally, a persistent racial gap in glycemic control between African Americans and non-Hispanic Whites was continually observed in the populations assessed during the systematic review.…”
Section: Racial Differences In Diabetes Outcomesmentioning
confidence: 99%
“…For example, children with type 1 diabetes from racial/ethnic minority populations with lower socioeconomic status are at risk for poor metabolic control and poor emotional functioning (47). Significant racial differences and barriers exist in self-monitoring and outcomes (48).…”
Section: Access To Health Carementioning
confidence: 99%
“…A recent study (4) in the 26 states and District of Columbia that expanded Medicaid under the Affordable Care Act found that diabetes diagnoses increased by 23% in 2014 compared with the previous year. Hispanic individuals in the U.S. experience higher rates of type 2 diabetes and, once diagnosed, exhibit poorer glycemic control than non-Hispanic white individuals (3,5). …”
Section: Introductionmentioning
confidence: 99%